2021
DOI: 10.1177/07349041211013698
|View full text |Cite
|
Sign up to set email alerts
|

A review on fire suppression by fire sprinklers

Abstract: Water spray remains the most effective, environment-friendly and economical way of fighting accidental or unwanted fires, and this is largely due to its thermal characteristics. The mechanism of fire suppression by sprinkler water sprays is influenced by numerous factors, which have been the focus of years’-long and on-going research studies to improve its extinguishing performances. A comprehensive review study was carried out in this study to assess the level of technological know-how and current state of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Field testing is necessary to accurately capture the real behavior of water mist systems in response to a fire event [15]. Previous evaluations of the combined use of water mist and fire suppression mechanisms primarily focused on the general characteristics of the fire plume, such as its geometry, temperature, gas flow speed, and smoke quantity [16][17][18] and found that larger droplets are more effective in penetrating a smoke layer.…”
Section: Introductionmentioning
confidence: 99%
“…Field testing is necessary to accurately capture the real behavior of water mist systems in response to a fire event [15]. Previous evaluations of the combined use of water mist and fire suppression mechanisms primarily focused on the general characteristics of the fire plume, such as its geometry, temperature, gas flow speed, and smoke quantity [16][17][18] and found that larger droplets are more effective in penetrating a smoke layer.…”
Section: Introductionmentioning
confidence: 99%
“…The suppression mechanisms for conventional fire sprinklers and water mist systems are distinct from each other as a result of their difference in size of water droplets. Vast numbers of large-scale fire experiments have been carried out to study the interaction between fire plumes and water-based suppression systems [12][13][14], where fire sprinklers utilise large diameter water droplets in order to cool down the flame and combustible materials' surface [15,16], while water mist applies water droplets with sizes smaller in few orders of magnitudes. With smaller droplets, water mist systems suppress fire by cooling flame surface and volumetric displacement of combustive gas [17].…”
Section: Introductionmentioning
confidence: 99%